Interferência da redução no volume de aplicação sobre o controle da mancha preta (Guignardia citricarpa Kiely) em frutos de laranja 'Valência' - Araújo, Demétrius De [UNESP]; Raetano, Carlos Gilberto [UNESP]; Ramos, Hamilton Humberto; Spósito, Marcel Belatto; Prado, Evandro Pereira [UNESP] (Grupo Paulista de Fitopatologia, 2013)
The chemical control of the causal agent of citrus black spot (CBS) has been highlighted for the excessive required number of sprayings, considerably increasing citrus production costs. Improvements in the spray efficiency and reductions in the quantity of phytosanitary products have already been searched, but the results of that practice are not consistent yet for its use at commercial scale. Thus, the aim of the present study was to evaluate the interference of reduced spray volumes in black spot control in citrus fruits. The experiment was carried out in commercial citrus orchard with 16-year-old plants of 'Valencia' variety, during 2007 agricultural season. Treatments consisted of three spray volumes: 3.5; 4.5 and 8.5 liters.plant-1, applied with Arbus 2000/Export airblast sprayer with special manifold of hydraulic nozzles, using fungicides and periods recommended for the disease control, totaling four sprayings plus a control treatment (without spray). The disease incidence and severity were evaluated by visual diagrammatic scale of notes in two different periods (preharvest and harvest), at three plant heights (low, middle and top) and three horizontal sections (entrance, frontal and exit) in two sides of the plant. The fallen fruits were counted every fifteen days, for previously selected plants, from the beginning of maturation to harvest, and the production was quantified (kg.plant-1). The disease incidence and severity were significantly lower when sprayings were done with 8.5 liters.plant-1 in the first evaluation period (pre-harvest), but in the harvest period there were not differences between the same parameters when 4.5 or 8.5 liters.plant-1 were sprayed. None of those treatments reduced the disease on the top section of plants, compared to control. The plant sections with fruits more exposed to sun rays, top and right side of the plant, demonstrated higher disease incidence and severity. The volume reduction from 8.5 to 4.5 liters.plant-1 can be adopted for citrus orchards without damaging the CBS control level.

O controle químico do agente causal da mancha-preta-dos-citros (MPC) tem merecido destaque pelo excessivo número de pulverizações, elevando sobremaneira os custos de produção na citricultura. A busca por melhorias na eficiência das pulverizações e reduções na quantidade dos produtos fitossanitários já tem sido realizada, mas os resultados dessa prática ainda não são consistentes para que possa ser aplicado em escala comercial. Sendo assim, essa pesquisa objetivou avaliar a interferência da redução no volume de aplicação, sobre o controle químico da mancha preta em frutos cítricos. O experimento foi conduzido em pomar comercial com plantas de 16 anos de idade, da variedade Valência durante o ano agrícola 2007. Os tratamentos consistiram de três volumes de calda, 3,5; 4,5 e 8,5 L planta-1, aplicados por pulverizador de jato transportado Arbus 2000/Export, com ramal especial de bicos, utilizando-se fungicidas e períodos recomendados para o controle da doença em um total de quatro pulverizações e mais um tratamento testemunha (sem pulverização). As avaliações de incidência e severidade da doença ocorreram através de escala visual diagramática de notas em duas épocas (pré-colheita e colheita), em três alturas (baixo, médio e alto) da planta e mais três setores horizontais (entrada, frontal e saída) em dois lados da planta. Os frutos caídos foram contados quinzenalmente, em plantas previamente selecionadas, do início da maturação até a colheita com a quantificação da produção (kg planta-1). A incidência e severidade da doença foram menores quando as pulverizações foram realizadas com 8,5 L planta-1 na primeira época de avaliação (pré-colheita), porém na colheita, não houve diferenças entre os mesmos parâmetros, quando pulverizados 4,5 ou 8,5 L planta-1. Nenhum tratamento reduziu a doença no setor alto da planta, em comparação a testemunha. Os setores da planta com os frutos mais expostos aos raios solares, lado direito e alto da planta, apresentaram maior incidência e severidade da doença. A redução no volume de 8,5 para 4,5 L planta-1 pode ser praticada na citricultura sem prejuízo do nível de controle da MPC.
Interference of spray volume reduction in citrus black spot (Guignardia citricarpa Kiely) control in 'Valência' citrus fruits
Keywords: tecnologia de aplicação; citros; controle químico; application technology; citrus; chemical control